PROSEDUR MANAJEMEN KELAS - Uripin, Puji (Penerbit CV Tentrem Karya Nusa, 2018)
The teacher will not success to create the good learning process without planning, organizing, directing, supervising the class. Before learning begins the teacher must manage the class well until the learning process is completed. The class management is an activity to create and maintain optimal conditions for an effective and efficient teaching and learning process. The class management is intended to create good conditions of the class which allows students to actaccording to their abilities. The class management procedures include preventive dimensions and curative dimensions, all of which are efforts to create effective and efficient learning processes to achieve the learning goals.Key Words: Procedure, Class Management